PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID MATA KULIAH KEBIJAKAN VOKASI KETEKNIKAN PADA PROGRAM PEMINATAN TECHNOPREUNERSHIP DAN INOVASI - Budiarsa, M. Sesar; Wibowa, Basuki; Sukardjo, M (Jurnal Pendidikan Teknik dan Vokasional, 2021)
This research aims to develop learning medium with vocational and technical for android, bades on matter expert and media expert. This research adapted from ADDIE development model which is a type of Research and Development (R&D) there are 5 stages include: 1) Analysis, 2) Design, 3) Development, 4) Implementation, and 5) Evaluation, but the research is only carried out until the Implementation phase. Validation of the media is done by one matter expert and one media expert.This results showed that the level of media feasibility with vocational and technical for android as a medium learning based on assessment: 1) subject matter expert obtained a total score of 65 and percentage scored 74%, 2) media expert obtained a total score of 69 and percentage scored 78,5%. The vocational and technical medium for android is feasible to use. Keywords: ADDIE, android, learning medium